Knowledge Attitude and Practice of Dengue Syndrome Management on the Basis of National Guideline by the Physicians of Dhaka City - Islam, Mohammad Rafiqul; Biswas, Sarmistha; Amin, Mohammad Robed; Rahman, Md Ridwanur (Journal of Medicine, 2021)
Objectives: Dengue is the fastest emerging arboviral infection. It was expected that the National Control Program will promote the use of the revised and updated version of the guideline for uniform clinical management of Dengue/DHF in the country with a view to reduce case fatality due to dengue. We tried to assess the knowledge attitude and practice of different tier of physicians on the basis of this guideline. Method: Total 317 physicians from academic hospital, 57 physicians from non-academic hospital and 21 private practitioners took part in the survey. Results: knowledge and attitude regarding management protocol of Dengue syndrome were significantly (p<0.05) associated with different academic tier but practice was not significantly (p<0.05) associated with different academics. The mean of accurate knowledge regarding management protocol of Dengue syndrome was significantly (p<0.05) associated with training status but attitude and practice were not significantly (p<0.05) associated with training status. Conclusion: This study reveals that physicians possibly didn’t went through the dengue guideline properly as their knowledge, attitude and practice were poor in each tier of professional practice. But dengue training improved knowledge regarding management of patients. J MEDICINE JAN 2021; 22 (1) : 18-21